2006
DOI: 10.1074/jbc.m602440200
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Degrades Amyloid-β Fibrils in Vitro and Compact Plaques in Situ

Abstract: The pathological hallmark of Alzheimer disease is the senile plaque principally composed of tightly aggregated amyloid-␤ fibrils (fA␤), which are thought to be resistant to degradation and clearance. In this study, we explored whether proteases capable of degrading soluble A␤ (sA␤) could degrade fA␤ as well. We demonstrate that matrix metalloproteinase-9 (MMP-9) can degrade fA␤ and that this ability is not shared by other sA␤-degrading enzymes examined, including endothelinconverting enzyme, insulin-degrading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
315
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(327 citation statements)
references
References 56 publications
8
315
2
2
Order By: Relevance
“…Although the animals were received Aβ intracerebroventricularly, however, via plasma clearance of Aβ, the extract can help to decrease the Aβ level in brain. Since systemic clearance of Aβ, especially by the liver, could determine the plasma levels of Aβ available for transport into the brain across the blood-brain barrier [9,15] it can be concluded that the lavender may undergo the liver clearance of Aβ. However, probable direct effect of the medicine on the Aβ plaques in the brain requires crossing the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the animals were received Aβ intracerebroventricularly, however, via plasma clearance of Aβ, the extract can help to decrease the Aβ level in brain. Since systemic clearance of Aβ, especially by the liver, could determine the plasma levels of Aβ available for transport into the brain across the blood-brain barrier [9,15] it can be concluded that the lavender may undergo the liver clearance of Aβ. However, probable direct effect of the medicine on the Aβ plaques in the brain requires crossing the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Also phagocytosis of Aβ plaques by microglia can restrict its accumulation in the brain [13]. Microglia also secrete proteolytic enzymes that degrade Aβ, such as insulin-degrading enzyme, neprilysin, matrix metalloproteinase 9, and plasminogen, further suggesting a neuroprotective role for these cells in AD [14,15]. However, persistent Aβ accumulation despite increasing microglial numbers suggests that the ability of microglia to clear Aβ may decrease with age and progression of AD pathology [13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, sometimes the activated microglia in BM-MSCtreated mice contained Ab (data not shown). Microglia secrete proteolytic enzymes that degrade Ab, such as insulin-degrading enzyme (IDE), neprilysin (NEP), matrix metalloproteinase 9 (MMP-9), and plasminogen [21,22].…”
Section: Decreased Ab Deposition Following Transplantation Of Bm-mscsmentioning
confidence: 99%
“…The proteolytic efficiency with which plasmin degrades fibrillar Aβ, however, is approximately 1% of that for freshly dissolved (i.e., largely monomeric) Aβ [17]. A recent study demonstrated that MMP-2 and -9 degrade Aβ fibrils in vitro [19]. However, the ability of plasmin or MMPs to degrade Aβ aggregates in AD-related animal models remains to be established.…”
Section: Proteases That Degrade Aβmentioning
confidence: 97%
“…Known Aβ-degrading enzymes include neprilysin (NEP), insulin-degrading enzyme (IDE), matrix metalloproteinases (MMPs), endothelincoverting enzyme (ECE), angiotensin-converting enzyme, the plasmin system and CatB [14][15][16][17][18][19][20]. Studies in knockout mice demonstrated that NEP, IDE, ECEs and MMP-2 or -9 are involved in degrading endogenous murine Aβ [16,21,22].…”
Section: Proteases That Degrade Aβmentioning
confidence: 99%